2004
DOI: 10.1111/j.1600-6143.2004.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Extending Medicare Coverage of Immunosuppressive Medications to the Life of a Kidney Transplant

Abstract: Unless they maintain Medicare status through disability or age, kidney transplant recipients lose theirMedicare coverage of immunosuppression 3 years after transplantation. A significant transplant survival advantage has previously been demonstrated by the extension of Medicare immunosuppressive medication coverage from 1 year to 3 years, which occurred between 1993 and 1995. The United States Renal Data System (USRDS) was analyzed for recipients of kidney transplants from 1995 to 1999. Using a Markov model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 16 publications
0
71
0
Order By: Relevance
“…Woodward et al (24) have shown that extending the coverage from 1 yr to 3 yr posttransplantation has eliminated the 4.5% difference in graft survival between low-income and high-income recipients. In a follow-up analysis (25), the same authors estimated that if Medicare provided life-long immunosuppressive medications to all of the recipients, then graft failure would be reduced by 1.2% annually beginning in the fourth year posttransplantation. Furthermore, Medicare beneficiaries who are eligible to receive the immunosuppressive medication coverage must still pay 20% of the cost of these medications as Medicare covers only 80% of the total cost.…”
Section: Discussionmentioning
confidence: 99%
“…Woodward et al (24) have shown that extending the coverage from 1 yr to 3 yr posttransplantation has eliminated the 4.5% difference in graft survival between low-income and high-income recipients. In a follow-up analysis (25), the same authors estimated that if Medicare provided life-long immunosuppressive medications to all of the recipients, then graft failure would be reduced by 1.2% annually beginning in the fourth year posttransplantation. Furthermore, Medicare beneficiaries who are eligible to receive the immunosuppressive medication coverage must still pay 20% of the cost of these medications as Medicare covers only 80% of the total cost.…”
Section: Discussionmentioning
confidence: 99%
“…Complications due to nonadherence can result in increased physician visits and inpatient hospitalization stays and, in cases of kidney transplantation failures, re-initiation of dialysis, all culminating in increased overall health care costs. [11][12][13][14][15] Immunosuppressant therapy is costly, with an annual medication regimen expense of approximately $30,000 during the first year after transplantation and $15,000 every year thereafter. 16,17 In order to improve quality of care and possibly reduce overall medical costs, health plans are looking increasingly to specialty pharmacy programs and/or specialty pharmacies to address the challenges of managing transplant patients taking oral immunosuppressive therapy.…”
Section: Managing Specialty Medication Services Through a Specialty Pmentioning
confidence: 99%
“…[2][3][4][5][6][7] After 5 years, only 35% of dialysis patients are still living, compared with 70% to 80% of patients who receive a deceased or living-donor transplant. 1 Thus, to promote ongoing quality improvement, the Centers for Medicare and Medicaid Services (CMS) Conditions for Coverage (CfC) for ESRD Facilities mandate that accredited dialysis centers provide evidence of transplant education, track patients' transplant referrals and status on the waiting list, and communicate with transplant facilities regularly ( Table I).…”
mentioning
confidence: 99%